CaSSIS-based stereo products for Mars after three years in orbit. (15th September 2022) - Re, Cristina; Fennema, Audrie; Simioni, Emanuele; Sutton, Sarah; Mège, Daniel; Gwinner, Klaus; Józefowicz, Mateusz; Munaretto, Giovanni; Pajola, Maurizio; Petrella, Amedeo; Pommerol, Antoine; Cremonese, Gabriele; et al.
Abstract: The Colour and Stereo Surface Imaging System (CaSSIS) on board the ExoMars Trace Gas Orbiter (TGO), operating in push-frame mode, provides multiband images at four different wavelengths thanks to a Filter Strip Assembly with a panchromatic filter and three broadband filters within the visible and near infrared range. The camera acquires stereo pairs fundamental for the initialization of the photogrammetric process to perform three-dimensional reconstruction of the Martian surface at the best resolution of 4.6 m per pixel for regions up to ∼400 km 2 in one imaging sequence. The 3D points derived from the stereo processing are used to generate Digital Terrain Models (DTMs) with height accuracy on the order of one image pixel on ground allowing high-resolution morphometric studies and in general improving the understanding of the geology and geomorphology of the surface of Mars. This work provides a review of the CaSSIS stereo products supported by a description of the applied methods and examines some specific approaches directed to science analysis. Furthermore, our development of methods is herein focused on the proof of concept and the performance of our dedicated pipeline. The DTM generation procedure has been implemented in a stereo photogrammetric pipeline by the team of the National Institute for Astrophysics-Astronomical Observatory of Padova (INAF-OAPd). The workflow is based on area-based image matching integrated in a multi-resolution approach where the quality of the image matching largely determines the quality of the output DTM. For this reason, the influence of the parameters involved in the matching process (i.e. number of tie-points, template sizes and shape models in matching) has been studied. CaSSIS stereo products have been generated for approximately 0.1% of the surface of Mars and 16.3% of the total stereo images acquired so far. In this work, some scientifically interesting targets have been considered in the investigation to provide an overview of the quality of the stereo results. The experimental studies related to stereo analysis frequently led to comparison tests since they represent the best approach for contributing to the methodological consolidation of the photogrammetric data processing. The quality assessment based on comparison with reference terrain data is very promising also in considering areas with different surface type and morphologies. Graphical abstract: Image 1 Highlights: Pipeline for the generation of Digital Terrain Models and Anaglyphs. Quality assessment. Image content. Morphological characteristics. Comparisons with reference DTMs.